An Earlier terminus ante quem for the Epistle of James?: The Influence of James on Clement of Alexandria’s Transmission of 1 Clement 17 - List, Nicholas (The catholic biblical quarterly, 2024)
The current terminus ante quem for the Epistle of James is the third century, with the first clear quotations of the epistle located in Origen. Aside from a few contentious correspondences with the Apostolic Fathers, no earlier allusions to James have received any serious consideration. I argue that an earlier reference should in fact be detected in Origen’s predecessor, Clement of Alexandria. In book 4 of his Stromata, the Alexandrian quotes from 1 Clement 17, a text that presents the figure of Job as an exemplum of humility. Clement significantly alters his source text in such a way that seems to betray knowledge of James, producing a synthesis of Joban tradition in early Christianity. If this claim is substantiated, it would effectively push the terminus ante quem for James back by one generation, to the late second century c.e.